ҚУЙИ АМУДАРЁ СОҲИЛИДАГИ XVI-XIX АСРЛАРДА ЮЗ БЕРГАН ЭТНОСИЁСИЙ ВА ЭТНОМАДАНИЙ ЖАРАЁНЛАР ТАРИХНОМАСИ - Шерниязов, Р.Х. (SCIENCE and SOCIETY, 2024)
Political and ethnic processes in the lower reaches of the Amudarya basin, ethnonyms found in folklore and field research by local historians and ethnographers and the relationships between the Uzbek, Kazakh, Karakalpak, Turkmen and Turkic peoples in general, the ethnic composition of the Karakalpaks in particular the ethnogeography of the “Aral Uzbeks” are quite clearly presented . In this article you can get acquainted with the factors that played a special role in the ethnic formation of a number of Turkic peoples.
Keywords: lower Amudarya; K.L. Zadikhina; B.V. Andrianova; S.K. Kamalov; Kh. Esbergenov; M. Tleўmuratov; “Aral Uzbeks”; Shakhtemir; Kichik zhuz; Askabakli-ata